An evaluation of an African UNESCO-inscribed intangible cultural heritage jerusarema/ mbende dance of Zimbabwe - Mapira, Nesta Nyaradzo (2018)
The jerusarema/mbende dance, inscribed by UNESCO in 2005 as an “oral and intangible cultural heritage”, appears to face extinction three years later as UNESCO listed the factors endangering its authentic elements from various aspects, including choreography, costume, instrumentation and song type. The dance originated from the Zezuru people of Mashonal and East Province of Zimbabwe and has been performed in the pre-colonial, colonial and post-colonial eras. After its inscription, programs to safeguard the authenticity of the dance were implemented and recorded for documentary purposes. However, there has been no evaluation of the authenticity of the dance elements used during performances since the designation of UNESCO heritage status. Therefore, this study utilised the enlisted authentic elements of jerusarema/mbende dance as benchmarks to evaluate the degree to which practitioner adhere to the authenticity of the dance elements during performances from 2013 to 2015. These benchmarks include acrobatic and sensual movements; waist shaking and hip movements by women; movements by men who crouch while jacking both arms and vigorously kick the ground with the right leg to imitate a burrowing mole; rattles, wooden clappers and mitumba drums as instruments; hand clapping, yodelling, whistle blowing by women and the omission of songs and lyrics. By using a qualitative research method through online research, data were collected primarily in form of interviews and from secondary sources which were archival records. Both primary and secondary data sources were selected purposively by using criterion sampling. Ten dance practitioners (four trainers, three directors, two dancers and one drummer) from the Mashonal and East Province of Zimbabwe who have hands on experience with jerusarema/mbende dance gave an outline of what they perceived to be authentic to the dance. Seven dance ensembles (four senior and three junior) picked using their experience and attendance at the Jerusarema Mbende Annual Festival from 2013 to 2015, provided the researcher with evidence of the elements used during formalised performances. The results showed that some elements of the dance listed by UNESCO have been maintained during the dance performances, for example, dance movements and instruments mentioned as benchmarks. However, there are innovations such as the use of dance movements from other music genres, songs with lyrics, a pelvic thrust to end each active dance session, and a showcase of wood clapping skills all of which deviate from the authentic benchmarks. The number of drums and type of rattles mentioned by the dance practitioners are not listed by UNESCO. Furthermore, deviations from UNESCO listed authentic elements are noticed in jerusarema/mbende dance performances. Hand clapping has been abandoned and yodelling and whistle blowing are under the threat of complete disappearance. All these discrepancies are influenced by different names used to refer to the dance, unconventional performance context and arbitrary interest among youth. Despite the UNESCO inscription, the dance is still in danger of extinction and is prone to changes and developments whilst some of the authentic elements are being maintained. Generally, oral and intangible cultural heritage management and revival of jerusarema/mbendedance seem problematic. Therefore, there is a need to remind jerusarema/mbendedance performers, the custodians of this dance, to protect the authentic elements. The researcher hopes that the results will contribute towards the improvement of the safeguarding program of jerusarema/mbendedance and the protection of the authentic elements.